PERLINDUNGAN HUKUM BAGI PARA PIHAK DALAM PERJANJIAN JUAL BELI ONLINE MELALUI SISTEM JASA TITIP - Litamahuputty, Fransisca Octaviane; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
In the current era of globalization, various aspects of people's lives are influenced by advances in information and communication technology, including business developments. In this regard, online application-based services are a competitive demand that requires the role of technology in facilitating people's mobility. Currently, the online buying and selling business is growing rapidly, over time this has changed people's shopping habits. where people feel that this is quite more efficient in saving time and not least from the view of society in general that they can buy the goods they want at much cheaper prices. So this habit opens up opportunities for business people, especially in the field of online buying and selling services (jastip ) is a service for purchasing certain goods offered via social media. In general, online entrustment services are only regulated in the Civil Code and Law Number 19 of 2016 concerning Electronic Information and Transactions and Government Regulation Number 71 of 2019 concerning Implementation of Electronic Systems and Transactions . The courier service acts as an intermediary between the seller and the buyer, whose job is to purchase the buyer's goods by taking photos of branded goods in the shop that are currently popular and then publishing them via social media.